(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
It is always useful and timely for teachers to go back to basic principles and to revise their teaching plans. It is important to remind yourself what you are doing, and why you are doing it. What do you hope to achieve? With these ideas in mind, teachers can then set specific goals for their teaching plans. This article will look at some basic teaching methods that can be applied to help achieve specific educational goals at the tertiary level. The implementation of ideas for improvement can often be lost if the teaching climate in which they are tried is not simple, structured and appropriate.